Physical Activity and Exercise in Dementia - Sefa Lok; Neslihan Lok (Psikiyatride Güncel Yaklaşımlar, 2015)
Aging is a dynamic process that affects many systems in the body. Cognitive function with aging, including memory, intelligence, personality and behavior are affected at different levels. As time passes, durability of individuals and the amount of physical activity and exercise decrease. Apart from normal aging process, accompanying chronic brain syndrome of dementia will further reduce activities. Physical activity can provide opportunities for individuals with dementia in the path to socialize. Therefore, the role of physical activity and exercise in adapting an active lifestyle to protect the health of individuals with dementia is becoming increasingly important. Physical activity and exercise which would help in improvement of cognitive activity in dementia are briefly reviewed in this article. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2015; 7(3.000): 289-294]